Potensi Pengembangan Kawasan Agrowisata Belimbing Karangsari, Kecamatan Sukorejo, Kota Blitar, Jawa Timur - Damas Sagita; Lury Sevita Yusiana; Anak Agung Keswari Krisnandika (Nandur, 2023)
Agrowisata Belimbing Karangsari is an agricultural tourism located in Blitar City. The condition of agro-tourism supporting facilities such as trash cans, rest areas, parking, toilets, and others has not been well planned. Tourism support facilities are closely related to tourism development attractions. Where in it must meet the three elements of the requirements for the formation of tourism development attractions. These elements consist of something to see (what can be seen), something to do (what can be done), something to buy (what can be bought). The purpose of this research is to identify, analyze, and provide solutions in the form of determining the development potential of the Agrowisata Belimbing Karangsari area. The research method used is a qualitative descriptive research method with data collection using a survey method. The stages of the research were carried out through several stages, namely preparation, inventory, analysis, synthesis, concept and concept development. The basic concept of this research is sustainable tourism which includes ecological sustainability, social adaptability, and cultural sustainability. The final result of this research is the activity recommendation in the illustration. There are three recommendations for the most important tourism activities, namely the manufacture of preparations from star fruit, culinary local food typical of Blitar City, and local cultural arts performances of Blitar City.